Exposure of pregnant consumers to suspected endocrine disruptors (Copenhagen, 2012)
"Pregnant women’s exposure to potential endocrine disruptors from consumer products, indoor environment and food has been investigated. A risk assessment has been made, taken the total exposure of endocrine disruptors into account. A number of suspected endocrine disruptors were selected based on their endocrine disruptive effects in animal studies, and anticipated exposure of pregnant women to the substances through consumer products, indoor air or food. The selected substances are for example selected phthalates, parabens, pesticides, bisphenol A and triclosan. The content and migration of the selected substances were analysed in 8 product groups (for example, covers for mobilphones, gloves and shoes). The analyses showed that none of the selected substances migrated from the products. The risk assessment is based on data from earlier reports from the Danish EPA for consumer products and from literature data for indoor environment and food. The risk assessment shows that there could be a risk when the total exposure from consumer products, indoor environment and food is taken into account. There is a need for pregnant women to reduce the exposure to endocrine disruptors from food, indoor environment and consumer products, and it is important to take the total exposure into account."